Cultural values and career goal of employees in a Malaysian industrial corporation - Ismail, Maimunah; Abdul Rahim, Atikah Nadia (2016)
This paper presents a study on the influence of cultural values (self-direction, achievement, tradition, and benevolence) on career goal of employees in an oil and gas corporation in Malaysia. The study used the Social Cognitive Career Theory to support the theoretical framework of the investigation. Data gathered from 87 employees of an oil and gas corporation in the area of Kuala Lumpur were used in the analysis. The results show that the levels of the four cultural values experienced by the respondents are high while for the career goal is moderate. The regression results reveal that the predictor variables explain 28.0% of the variance in the career goal of the employees. Recommendation for human resource management and future research are discussed.